Establishment of in vitro culture of clinacanthus nutans (Burm. f.) lindau and antibacterial assay of different crude methanolic extracts - Lim, Cherrie Han Rou (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Clinacanthus nutans (Burm f.) Lindau or Sabah Snake Grass from the Acanthaceae family is a well-known medicinal plant and has been widely used in many Asian countries especially in Malaysia, Thailand, Indonesia, and China. The present study was aimed to establish axenic in vitro cultures, induce shoot and callus from axenic explants, evaluate antibacterial activities of the plant’s crude methanolic extracts, and analyze the phytochemical components present in the plant extracts. Results showed that explants soaked in 10% Clorox® for 15 minutes produced the highest percentage of axenic leaf explants (98%). Treatment with 15% Clorox® for 20 minutes and additional initial step of washing explants in diluted dish wash liquid was the best to produce contamination-free internodal (96.67%) and nodal explants (100%). The efficiency of plant regeneration via direct organogenesis from axenic nodal explants (source: mother plant and in vitro plantlet) was tested on Murashige and Skoog (MS) medium supplemented with BAP, IBA or TDZ at different concentrations (0.0- 2.0 mg/L) either alone and in combinations. Control medium without plant growth regulator (PGR) was found to be the best for shoot proliferation as it successfully produced healthier plantlets with longer shoots and vigorous roots within eight weeks when compared to other treatments. The effect of BAP alone, BAP in combination with 2, 4-D, and BAP in combination with NAA (0.0- 4.0 mg/L) was evaluated on the callus induction and formation. Explants cultured on the medium including 2, 4-D or without any PGR failed to form callus after eight weeks. The results showed that 100% of internodal explants culturing on MS medium supplemented with BAP alone or in combination with NAA produced callus. Leaf explants was not suitable for callus induction due to the poor performance of callus growth, hence, only internodal explants cultured on the medium fortified with 1.0 mg/L BAP under light condition was chosen for mass production of callus for the use of successive experiments. Subsequently, callus culture, leaf and stem from both in vitro plantlets and potted grown plants were extracted using methanol. The percentage of extraction yields for in vitro cultures (8- 19%) were higher than potted grown plant (< 5%). The crude methanolic extracts of C. nutans were then screened for its antibacterial activity and phytochemical composition by gas chromatography-mass spectrometry (GC-MS) analysis. Plant extracts were tested against Bacillus cereus, Listeria monocytogenes, Salmonella typhi and Echerichia coli using agar disc diffusion, and broth dilution to determine minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The results showed that all extracts exhibited bacteria inhibition. B. cereus was inhibited by all plant crude methanolic extracts with larger inhibition zone compared to other bacteria while potted grown leaf extract exhibited the greatest inhibition diameter in agar disc diffusion (19.38 mm). In broth dilution test, callus and potted grown leaf extracts again presented the best bioassay activity against B. cereus, with the MIC and MBC value at 3.13 mg/mL. From the GC-MS analysis, the components revealed from the crude methanolic extracts of C. nutans are mainly composed of hydrocarbon, followed by ester compounds. Alcohol, aromatic compounds, and aldehyde were also found. Several bioactive compounds that may have contributed to the antibacterial activities were detected.